Digital Business Marketing Assistance for Batik UMKM Actors in Klampar Village, Proppo District, Pamekasan Regency - Samsuki; Angraini, Merie Satya (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This mentoring activity in Klampar Village, Proppo District, Pamekasan, focuses on economic development through the MBKM KKN-T UTM 2024 program. The aim is to optimize local resources and enhance human resources by targeting strategic development areas. The proposed program, themed “Mentoring for Financial Management and Digital Business Marketing for UMKM Batik Actors,” addresses key issues such as the lack of financial separation between personal and business funds, limited capital, and a shortage of workers despite the high quality of local batik products. Method: The approach involves community training through socialization and counseling on financial management and digital marketing to support MSME growth. Practical Application: Digital marketing on e-commerce platforms can help MSMEs expand their market and income. Proper mentoring and access to relevant training are essential for improving digital literacy and competitiveness. Conclusion: Effective support enables MSMEs to manage finances and online marketing, promoting sustainable business development.